Estudo de estratégias de controle dos processos internos de um motor de combustão interna de injeção direta de etanol turbo - alimentado para maximização da eficiência global - Thiago Rodrigo Vieira da Silva (2017)
The current energy sources and climatic world condition require the development of more efficient and sustainable internal combustion engines. In order to accomplish this requirements, the regulator agencies establish long goal of fuel consumption and greenhouse gases emissions. The evolution of engine designs, in order to achieve this long goals, is characterized by the use of new technologies such as, fuel direct injection, turbochargers, continuously variable valve timing, exhaust gas recirculation, variable compression ratio, among others, in downsized engines that running, preferably, with biofuels. The combination of the new technologies with the engine concept and alternative fuels must be managed and applied throughout the engine road map aiming to reduce the fuel consumption and the emissions. Therefore, this work aimed to characterize and analyze the control strategies of direct injection turbocharged internal combustion engine fueled by Brazilian ethanol in order to maximize the fuel conversion efficiency. The engine road map control strategies, proposed by this work, was divided in regions of different engine operating conditions, where each region was characterized by a specific engine control strategy. The five engine control strategies to maximize the fuel conversion efficiency establish in this work were: Lean Stratified Combustion Spark Ignition SCSIS, Lean Boosted Direct Injected LBDI, Homogeneous Charge Spark Ignited with Exhaust Gas Recirculation HCSI + EGR, Homogeneous Charge Spark Ignited HCSI, and Stratified Combustion to Pre-Ignition Suppression SCPIS. The obtained results from the use of these engine control strategies show an increase in the fuel conversion efficiency of 32% and 15,9% running on SCSIS strategy, 3,7% running on LBDI strategy and 1,8% running on SCPIS strategy, keeping satisfactory emissions levels.